1999
DOI: 10.1128/jvi.73.2.1001-1009.1999
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus DNA Replication Compartments in a Transient DNA Replication System

Abstract: Many DNA viruses replicate their genomes at nuclear foci in infected cells. Using indirect immunofluorescence in combination with fluorescence in situ hybridization, we colocalized the human papillomavirus (HPV) replicating proteins E1 and E2 and the replicating origin-containing plasmid to nuclear foci in transiently transfected cells. The host replication protein A (RP-A) was also colocalized to these foci. These nuclear structures were identified as active sites of viral DNA synthesis by bromodeoxyuridine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(28 citation statements)
references
References 76 publications
2
23
0
3
Order By: Relevance
“…Recent studies suggest a role for both of these proteins in specific regulation of the Arf promoter and subsequent modulation of cell cycle kinetics (Aslanian et al, 2004). We also observed E2F2 protein to be localized to intranuclear bodies that may coincide with ND10 bodies, which are sites for replication of many DNA tumor viruses, including HPV (Swindle et al, 1999). In support of this idea, E2F2 has been shown to associate with proteins involved in recombinational DNA repair, Mre11 and Nbs1, at both viral and cellular origins of replication (Maser et al, 2001).…”
Section: Discussionsupporting
confidence: 56%
“…Recent studies suggest a role for both of these proteins in specific regulation of the Arf promoter and subsequent modulation of cell cycle kinetics (Aslanian et al, 2004). We also observed E2F2 protein to be localized to intranuclear bodies that may coincide with ND10 bodies, which are sites for replication of many DNA tumor viruses, including HPV (Swindle et al, 1999). In support of this idea, E2F2 has been shown to associate with proteins involved in recombinational DNA repair, Mre11 and Nbs1, at both viral and cellular origins of replication (Maser et al, 2001).…”
Section: Discussionsupporting
confidence: 56%
“…Alternatively, fluorescent dots might not always represent integrated DNA but normally replicating virus DNA. It has been shown that viruses, including HPV, replicate their genome at compartments or foci rather than randomly within the nucleus . Therefore, the HPV FISH probe might hybridize to the accumulated single‐strand DNA of such replication foci, mimicking the punctuate signals noted in the case of integration, thereby explaining the high prevalence of a punctuate pattern (70%) observed in the LSIL cases in the current study.…”
Section: Discussionmentioning
confidence: 69%
“…the viral origin. 9,35 However, E1 and E2 co-expressed in C33A cells harboring a plasmid with a HPV origin of replication do indeed co-localize with PML. 35 Furthermore, they co-localize with RP-A and BrdU staining indicating active sites of replication.…”
Section: Discussionmentioning
confidence: 99%
“…9,35 However, E1 and E2 co-expressed in C33A cells harboring a plasmid with a HPV origin of replication do indeed co-localize with PML. 35 Furthermore, they co-localize with RP-A and BrdU staining indicating active sites of replication. 35 However, for papillomavirus, neither the E2-dependent transcription nor viral DNA replication is reliant on the presence of PML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation